THE ROLE OF MR SPECTROSCOPY AND CONTRAST ENHANCED MRI IN PROSTATE CANCER DIAGNOSIS - Kostova, Masha; Jovanovska, Elizabeta Stojovska; Dejanova Panev, Sandra; Prgova Veljanova, Biljana; Veljanovski, Dimitar; Dodevski, Ace (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
In patients with increased prostate-specific antigen, the next diagnostics tool is transrectal ultrasound-guided biopsy. The biopsy can cause pain, bleeding and infection. Multiparametric magnetic resonance imaging (mp MRI) as non-invasive diagnostics tool is used as a triage test to avoid biopsy, as well as to improve the diagnostics. The aim of this study was to examine the value of MR spectroscopy and dynamic post-contrast series in the diagnosis of prostate cancer. This cohort prospective study included 100 patients from CGH “September 8 th ” with increased levels of PSA. The MRI equipment used was Siemens Essenza 1,5T with body coil. The results obtained by MR spectroscopy analysis were correlated with the post-contrast series, whereby by mapping suspicious areas, patients underwent biopsy according to the PIRADS (prostate imaging and reporting data system) classification. Of the 100 patients, 96 were biopsied according to the PIRADS (prostate imaging and reporting data system) classification. The MRI results and pathohistological findings were then compared. On MR postcontrast series, a malignant lesion was detected in 52% of patients, in 33% of patients the lesion was suspicious for malignancy. On MR spectroscopy, a choline+creatinine/citrate ratio of 0.8 to 2 indicating a possible malignant lesion was confirmed in 33% of patients, this ratio was greater than 2 in 33% of patients, indicating a lesion highly suspicious for malignancy. MR spectroscopy combined with contrast enhanced MRI is a powerful tool for non-invasive differentiation of benign prostatic hyperplastic nodule and prostatitis from a malignant nodule.   Key words: prostate, carcinoma, spectroscopy, IV contrast.